2008
DOI: 10.1021/cc800065a
|View full text |Cite
|
Sign up to set email alerts
|

TAC-Scaffolded Tripeptides as Artificial Hydrolytic Receptors: A Combinatorial Approach Toward Esterase Mimics

Abstract: In this report, we present the first library of tripodal synthetic receptor molecules containing three different, temporarily N-terminal protected peptide arms capable of performing hydrolytic reactions. To construct this library, the orthogonally protected triazacyclophane (TAC)-scaffold was used in the preparation of a split-mix library of 19 683 resin bound tripodal receptor molecules. For the construction of the peptide arms, three different sets of amino acids were used, each focused on one part of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…The further steps typically required for staining as previously described for other systems could thus be omitted 77. 79, 80, 83 Control experiments with blank beads (no peptide bound) and unspecific bead‐bound peptides showed that the observed color was indeed due to selective binding of hemin by particular peptide sequences and not, for example, by the bead material itself. The peptides each also contained a C‐terminal amino acid linker of six residues (BBBBRM) providing good accessibility for hemin, thus supporting specific binding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The further steps typically required for staining as previously described for other systems could thus be omitted 77. 79, 80, 83 Control experiments with blank beads (no peptide bound) and unspecific bead‐bound peptides showed that the observed color was indeed due to selective binding of hemin by particular peptide sequences and not, for example, by the bead material itself. The peptides each also contained a C‐terminal amino acid linker of six residues (BBBBRM) providing good accessibility for hemin, thus supporting specific binding.…”
Section: Resultsmentioning
confidence: 99%
“…Positive beads were collected and analyzed by two methods: PED‐MALDI TOF mass spectrometry as introduced previously by Pei et al78 and direct on‐bead sequencing by automated Edman degradation 79. 80 The latter was used as a control to evaluate whether cysteine‐containing sequences can be found by the PED‐MS method, which had previously been applied only to non‐cysteine‐containing libraries. In the past five years, in fact, only a few combinatorial library approaches in which cysteines have been included at partially randomized positions in peptide sequences have been described 79.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Tripodal peptidomimetics are also suitable for this purpose. Several tripodal peptides with different platforms have been designed as receptors of either organic molecules 16 or metal ions. [17][18][19][20][21][22][23][24][25][26][27][28][29] These ligands have several advantages in addition to the pre-organized structure and enhanced chelate effect.…”
Section: Introductionmentioning
confidence: 99%